The design of presumptive tax regimes - Mas-Montserrat, Mariona (OECD Publishing, 2023)
Presumptive tax regimes, also known as simplified tax regimes, simplify the tax compliance process for micro and small businesses. By reducing tax compliance costs and levying lower tax rates compared to the standard tax system, these regimes aim at encouraging business formalisation and compliance. They are particularly useful in situations where actual taxable income is difficult to quantify as a taxpayer's tax base is determined using alternative indicators. Although these regimes exist in many tax systems, they vary greatly in their design. This OECD working paper provides an analytical framework for characterising and comparing these regimes. It also highlights key design aspects that deserve further consideration and lists a series of best practices on the design and administration of these regimes
Keywords: Taxation